2019
DOI: 10.1371/journal.pone.0211897
|View full text |Cite
|
Sign up to set email alerts
|

A combined computational strategy of sequence and structural analysis predicts the existence of a functional eicosanoid pathway in Drosophila melanogaster

Abstract: This study reports on a putative eicosanoid biosynthesis pathway in Drosophila melanogaster and challenges the currently held view that mechanistic routes to synthesize eicosanoid or eicosanoid-like biolipids do not exist in insects, since to date, putative fly homologs of most mammalian enzymes have not been identified. Here we use systematic and comprehensive bioinformatics approaches to identify most of the mammalian eicosanoid synthesis enzymes. Sensitive sequence analysis techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 120 publications
0
23
0
Order By: Relevance
“…These authors related the secretion of a phospholipase A 2 (PLA 2 ) inhibitor with the suppression of the proPO activation in hemolymph and the alteration of cellular response. Despite no homologous genes were identified in D. melanogaster, Scarpati et al [47] found other genes involved in eicosanoid pathway that could be functional equivalents.…”
Section: Discussionmentioning
confidence: 99%
“…These authors related the secretion of a phospholipase A 2 (PLA 2 ) inhibitor with the suppression of the proPO activation in hemolymph and the alteration of cellular response. Despite no homologous genes were identified in D. melanogaster, Scarpati et al [47] found other genes involved in eicosanoid pathway that could be functional equivalents.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, cytosolic or membrane-bound PGES isomerizes PGH 2 to PGE 2 . Insects also have been considered to have all biosynthetic machinery to synthesize PGE 2 , as predicted in previous bioinformatics analysis of Drosophila melanogaster (Scarpati et al, 2019). Indeed, three different PLA 2 s have been identified in S. exigua and include one secretory PLA 2 and two cellular PLA 2 s. Also, COX-like peroxynectins have been identified and play a role in oxygenating AA (Park et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Thus, selective spz KD in hop Tum-l blood cells improves organismal viability, much as aspirin treatment does. We envision two possible mechanisms of action: (1) aspirin may block the activities of COX-like enzymes (Scarpati et al, 2019;Tootle and Spradling, 2008), which may, in turn, act through the NF-κB/STAT axis in hop Tum-l blood cells to reduce levels of pro-mitotic/pro-inflammatory proteins, or (2) it may directly block the observed cell cycle progression, for example, by interacting with cell cycle proteins. The anti-mitotic effects of aspirin and reduction in tumorigenesis in flies are consistent with reported salutary effects in epidemiological studies of cancer patients (Elwood et al, 2009;Qiao et al, 2018;Schreinemachers and Everson, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, C20 polyunsaturated fatty acid (PUFA)-fed flies generate hydroxyeicosatetraenoic acid (13-HETE) (Tan et al, 2016), an AA metabolite, suggesting that flies express enzymes for eicosanoid synthesis. Our computational studies show that many functional enzymes for eicosanoid biosynthesis are encoded in the fly genome, including two other COX-like enzymes in addition to Pxt (Scarpati et al, 2019). We therefore analyzed inflammation readouts in flies after aspirin treatment and searched for anti-inflammatory C18-derived PUFAs.…”
Section: Introductionmentioning
confidence: 99%